PEMBERDAYAAN PEREMPUAN MENGHADAPI MODERNISASI PERTANIAN MELALUI KELOMPOK WANITA TANI (KWT) PADA USAHATANI SAYURAN DI KECAMATAN BISSAPU KABUPATEN BANTAENG - Asriyanti Syarif (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2018)
This research aims to: (1) knowing the forms of women empowerment through women farmer group (KWT) in facing the modernization of agriculture, the programs undertaken, and the level of women participation in that groups. (2) Assess the social and economic impacts of women empowerment through women farmer groups (KWT). This research was in Kecamatan Bissapu Banteng Regency, choose samples of two groups of women farmers (KWT) Paranglabbua and Lemoa Sejahtera. Take sample by purposive sampling taking six people (chairman, secretary, treasurer and 3 member) from KWT Paranglabbua and Lemoa Sejahtera, and one agriculture extension agent. Technique data analysis are: (a) qualitative descriptive on: (1) forms of empowerment, (2) programs undertaken by each group and social impact. While (b) participation rate is used scoring technique. (c) the economic impact is related to contributions using contribution analysis.  The results of the research show that: The form of women empowerment in farmer group (KWT): socialization, routine meeting, demonstration in experiment garden, counseling and training of vegetable processing involving extension instructor. Women empowerment program: Provision of production facilities, , experimental garden, agricultural processing, and counseling. The participation in women farmers group is high because of the value of benefits obtained in the form of knowledge and skills. (4) Increasing the role of women (4). Expansion of the work sector from the domestic sector to the domestic and public sectors (agriculture sector). (4) Increasing communication and cooperation (4) . While the economic impacts are: (1) creating employment in the field of agriculture (2) adding value to agricultural products with processing technology utilization (3) contributing income of 7.03%.